A proposed severity classification of borderline symptoms using the borderline symptom list (BSL-23) - Kleindienst, Nikolaus; Jungkunz, Martin; Bohus, Martin (Borderline Personality Disorder and Emotion Dysregulation, 2020)
Background: The Borderline Symptom List (BSL-23) is a well-established self-rating instrument to assess the severity of borderline typical psychopathology. However, a classification of severity levels for the BSL-23 is missing. - Methods: Data from 1.090 adults were used to develop a severity classification for the Borderline Symptom List (BSL-23). The severity grading was based on the distribution of the BSL-23 in 241 individuals with a diagnosis of BPD. Data from three independent samples were used to validate the previously defined severity grades. These validation samples included a group of treatment seeking patients with a diagnosis of BPD (n = 317), a sample of individuals with mental illnesses other than BPD (n = 176), and a healthy control sample (n = 356). The severity grades were validated from comparisons with established assessment instruments such as the International Personality Disorders Examination, the Structured Clinical Interview for DSM-IV, the global severity index of the Symptom Checklist (GSI, SCL-90), the Global Assessment of Functioning (GAF), and the Beck Depression Inventory (BDI-II). - Results: Six grades of symptom severity were defined for the BSL-23 mean score: none or low: 0-0.3; mild: 0.3-0.7; moderate: 0.7-1.7; high: 1.7-2.7; very high: 2.7-3.5; and extremely high: 3.5-4. These grades received consistent empirical support from the independent instruments and samples. For instance, individuals with a severity grade of none or low were virtually free from diagnostic BPD-criteria, had a GSI below the normative population, and a high level of global functioning corresponding to few or no symptoms. Severity grades indicating high to extremely high levels of BPD symptoms were observed at a much higher rate in treatment-seeking patients (70.0%) than in clinical controls (17.6%) and healthy controls (0.0%). The BSL-23 score that best separated treatment-seeking BPD patients and clinical controls was 1.50, whereas the clearest discrimination of BPD patients and healthy controls was found at a score of 0.64. - Conclusions: The grades of BPD-specific symptom severity derived from the distribution of the BSL-23 scores received consistent empirical validation from established assessments for psychopathology. Future studies should expand this validation by including additional instruments e.g., to assess self-esteem, loneliness, connectedness, and quality of life.
Gesehen am 12.10.2020